Internal Architecture and Population Size of Acromyrmex subterraneus molestans (Hymenoptera, Formicidae) Nests: Comparison Between a Rural and an Urban Area - Santos Lopes, Juliane Floriano; Ribeiro, Laila Fieto; Brugger, Mariana Silva [UNESP]; Camargo, Roberto da Silva [UNESP]; Caldato, Nadia [UNESP]; Forti, Luiz Carlos [UNESP] (California State University, 2011)
Ant nests vary in their depth and internal complexity. They can be shallow or reach seven meters down into the soil, with many chambers connected by tunnels. In the case of leaf-cutting ants, the nest protects the colony and provides appropriate microclimate conditions for the ants and the symbiotic fungus garden. In the present study we compared the internal architecture and population size of Acromyrmex subterraneus molestans nests in an urban and a rural area. We excavated, molded and measured six nests in an urban area and five nests in a rural area. For each nest, we measured the total volume of fungus in the chambers and estimated the population by counting the workers, which were separated into four size classes. The nests of A. subterraneus molestans in the urban and rural areas were always found near the base of trees. In the urban area they were also found near the curb of sidewalks. Ants use old roots and debris to reinforce the structure of the nest tunnels and at the same time reduce the costs of excavation by taking advantage of pre-existing cavities. Nests from the rural area had only one chamber, whereas in the urban area they had up to four chambers. Fungus chambers showed non-defined shapes and were found near the soil surface, both in the urban and in the rural area. Closeness to the surface may pose a problem to the maintenance of the humidity levels required by the fungus garden. The accumulation of cut leaves over the nest, as observed for other species of leaf-cutting ants, in particular A. crassispinus, may be a strategy to solve this problem. Building superficial nests also helps reduce the costs of excavating, and saves energy in the transport of substrate to the fungus chamber. The nest tunnels were located in pre-existing cavities and almost always connected the external environment to the fungus chamber. There were also longer tunnels that opened at some distance from the nest. These tunnels allow an increase in the foraging area and reduce the risk of outside predation. With respect to population size, we noted that the small workers represented on average 50% of the population, with no difference between the proportion of workers of each size class between urban and rural nests. No significant differences were found in the volume of fungus between nests of the urban and rural area. There were no significant correlations between the volume of fungus and the total population of workers or the number of workers of each size class.
Keywords: leaf-cutting ants; nest architecture; Acromyrmex